2016
DOI: 10.1016/j.molcel.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

3D-CLEM Reveals that a Major Portion of Mitotic Chromosomes Is Not Chromatin

Abstract: SummaryRecent studies have revealed the importance of Ki-67 and the chromosome periphery in chromosome structure and segregation, but little is known about this elusive chromosome compartment. Here we used correlative light and serial block-face scanning electron microscopy, which we term 3D-CLEM, to model the entire mitotic chromosome complement at ultra-structural resolution. Prophase chromosomes exhibit a highly irregular surface appearance with a volume smaller than metaphase chromosomes. This may be becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
122
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 58 publications
12
122
0
1
Order By: Relevance
“…Use of 3D correlative light electron microscopy (3d-CLEM) allowed the determination of the HAC volume at prometaphase. Assuming a normal density of chromatin packing, this yielded an estimated size of 5.5 MB for the HAC, essentially identical to the 5.1 MB calculated from the molecular cloning analysis (Kouprina et al 2012;Booth et al 2016). This agreement confirmed that the packing density of the alphoid tetO HAC is comparable to the other endogenous chromosomes.…”
Section: The Synthetic Alphoid Teto Hac For Epigenetic Engineering Ofsupporting
confidence: 65%
See 2 more Smart Citations
“…Use of 3D correlative light electron microscopy (3d-CLEM) allowed the determination of the HAC volume at prometaphase. Assuming a normal density of chromatin packing, this yielded an estimated size of 5.5 MB for the HAC, essentially identical to the 5.1 MB calculated from the molecular cloning analysis (Kouprina et al 2012;Booth et al 2016). This agreement confirmed that the packing density of the alphoid tetO HAC is comparable to the other endogenous chromosomes.…”
Section: The Synthetic Alphoid Teto Hac For Epigenetic Engineering Ofsupporting
confidence: 65%
“…Whereas none of the de novo HACs constructed before were physically mapped in molecular detail, largely due to the fact that they contain huge blocks of repeated DNA, the containing, in addition to its kinetochore, chromosome scaffold (revealed by staining for condensin subunit SMC2) and a chromosome periphery compartment (revealed by staining for Ki-67) (Booth et al 2016). Use of 3D correlative light electron microscopy (3d-CLEM) allowed the determination of the HAC volume at prometaphase.…”
Section: The Synthetic Alphoid Teto Hac For Epigenetic Engineering Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true for its mitotic roles. Specifically, Ki-67 is required for formation of the mitotic perichromosomal layer (11, 12), a proteinaceous sheath that coats mitotic chromosomes (13,14). In this layer, Ki-67's large size and highly positively charged amino acid composition keep individual mitotic chromosomes dispersed rather than aggregated upon nuclear envelope disassembly, thereby ensuring normal kinetics of anaphase progression (15).…”
mentioning
confidence: 99%
“…It is performed by laser welding to join two adjacent pieces of genetic material. Unlike the tissues in laser tissue welding [24,25], chromosomes are very small in size and are extremely thin (about 0.5-0.7 μm for human chromosomes) [26]. To weld the two tiny pieces of chromosome together without thermal and mechanical damage upon them is a great challenge in biotechnology and optical engineering.…”
Section: Introductionmentioning
confidence: 99%